Lean Healthcare Analysis at Airlangga Health Service Center - Kartika, Nurullaily; Widayanti , Putri (Southeast Asian Business Review, 2024)
Dental is one of the polyclinics whose biggest problems are waiting times and patient queues. The waiting time and patient queues are a waste in Hospitals. This study aims to identify any waste that occurs in the dental polyclinic at the Airlangga University Health Service Center (PLK) by implementing lean healthcare. Then, provide suggestions for improvements to reduce or eliminate the identified waste. The researcher used a qualitative approach with the results of the big-picture mapping to illustrate the flow of patient care in the dental clinic and determined which activities were value-added (VA) and which were not value-added (NVA). Interviews and questionnaires were distributed in this study to parties who have a role in the service delivery process to patients, namely the dental clinic coordinator, dentist, dental nurse, and service admin. The study's results found 7 value-added activities and 4 non-value-added activities. Then, the researcher used VALSAT to choose the right tools and process activity mapping with the highest score. The results of the waste identification show the weight of waste overproduction at 0.21, waiting at 0.33, transportation at 0.12, inappropriate process at 0.05, unnecessary inventory at 0.12, unnecessary motion at 0.07, and defect at 0.10. Then, a fishbone diagram is used to find the root cause of the waste, and then lean hospital to propose improvements to reduce or eliminate waste in PLK.